Eminent domain : a comparative perspective - Kim, Il-chung, ed
"The taking of private property for development projects has caused controversy in many nations, where it has often been used to benefit powerful interests at the expense of the general public. This edited collection is the first to use a common framework to analyze the law and economics of eminent domain around the world. The authors show that seemingly disparate nations face a common set of problems in seeking to regulate the condemnation of private property by the state. They include the tendency to forcibly displace the poor and politically weak for the benefit of those with greater influence, disputes over compensation, and resort to condemnation in cases where it destroys more economic value than it creates. With contributions from leading scholars in the fields of property law and economics, the book offers a comparative perspective and considers a wide range of possible solutions to these problems"--